Parallel Chaotic Multisplitting Iterative Methods for the Large Sparse Linear Complementarity Problem (Journal of Computational Mathematics, 2001)
A parallel chaotic multisplitting method for solving the large sparse linear complementarity problem is presented, and its convergence properties are discussed in detail when the system matrix is either symmetric or nonsymmetric. Moreover, some applicable relaxed variants of this parallel chaotic multisplitting method together with their convergence properties are investigated. Numerical results show that high parallel efficiency can be achieved by these new parallel chaotic multisplitting methods.